Nucleic Acid–Based Therapeutics in Orphan Neurological Disorders: Recent Developments - Khorkova, Olga; Hsiao, Jane; Wahlestedt, Claes (Frontiers in Molecular Biosciences, 2021)
The possibility of rational design and the resulting faster and more cost-efficient development cycles of nucleic acid-based therapeutics (NBTs), such as antisense oligonucleotides, siRNAs and gene therapy vectors, have fueled increased activity in developing therapies for orphan diseases. In spite of the difficulty of delivering NBTs beyond the blood brain barrier, neurological diseases are significantly represented among the first targets for NBTs. As orphan disease NBTs are now entering the clinical stage, substantial efforts are required to develop the scientific background and infrastructure for NBT design and mechanistic studies, genetic testing, understanding natural history of orphan disorders, data sharing, NBT manufacturing and regulatory support. The outcomes of these efforts will also benefit patients with “common” diseases by improving diagnostics, developing the widely applicable NBT technology platforms and promoting deeper understanding of biological mechanisms that underlie disease pathogenesis. Furthermore, with successes in genetic research, a growing proportion of ‘common’ disease cases can now be attributed to mutations in particular genes, essentially extending the orphan disease field. Together, the developments occurring in orphan diseases are building the foundation for the future of personalized medicine. In this review we will focus on recent achievements in developing therapies for orphan neurological disorders.